Islamic Academic Supervision for Enhancing Counseling Services in Islamic Elementary Schools: A School Action Research Study - Muhammad Mana Arif Rifqi; Abdurrahman Abdurrahman; Najihah Abd Wahid Wahid (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
the foundation of all educational processes, including guidance and counseling services. However, counseling practices in many Islamic elementary schools are often implemented unsystematically and are not consistently based on sustainable Islamic counseling principles. As a result, students frequently experience difficulties in understanding learning materials, maintaining learning motivation, and managing their study time effectively. This study aims to examine the implementation of Islamic academic supervision conducted by the madrasah head as a strategy to foster guidance and counseling teachers in improving the quality of Islamic counseling services at Madrasah Ibtidaiyah Nurul Mun’im. The research employed a qualitative School Action Research design conducted in two cycles, consisting of planning, action, observation, and reflection stages. Data were collected through observations, in-depth interviews, and documentation, and analyzed qualitatively. The findings reveal that systematic and reflective Islamic academic supervision significantly improved the professional competence of guidance and counseling teachers in planning, implementing, and evaluating counseling services based on Islamic values. Counseling practices evolved from normative and advice-oriented approaches into more integrative and contextual guidance that promotes students’ spiritual awareness and character development. This study contributes to the development of Islamic teacher supervision models and provides practical guidance for enhancing the effectiveness and sustainability of counseling services in Islamic elementary schools.